2022
DOI: 10.1021/acs.molpharmaceut.2c00027
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of In Vivo Pharmacokinetic Parameters and Time–Exposure Curves in Rats Using Machine Learning from the Chemical Structure

Abstract: Animal pharmacokinetic (PK) data as well as human and animal in vitro systems are utilized in drug discovery to define the rate and route of drug elimination. Accurate prediction and mechanistic understanding of drug clearance and disposition in animals provide a degree of confidence for extrapolation to humans. In addition, prediction of in vivo properties can be used to improve design during drug discovery, help select compounds with better properties, and reduce the number of in vivo experiments. In this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
39
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 58 publications
9
39
0
Order By: Relevance
“…Figures S14, S16). Similar results were recently reported for the GP rat CLp model, calling for additional research needed into reliable quantification of uncertainty.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Figures S14, S16). Similar results were recently reported for the GP rat CLp model, calling for additional research needed into reliable quantification of uncertainty.…”
Section: Discussionsupporting
confidence: 87%
“…For example, if focusing on the drug-design stage results (i.e., in the absence of in vitro data), Obrezanova et al showed RMSLE values of 0.35, 0.31, and 0.57 for predictions of rat CLp, Vss, and oral F, respectively. 9 This result is comparable to our AutoGluon and GP average RMSLE values of 0.42, 0.39, and 0.57 for rat CLp, Vss, and oral F, respectively.…”
Section: ■ Discussionsupporting
confidence: 86%
See 3 more Smart Citations